Identifying community-driven priority questions in acoustic backscatter research - Lecours, Vincent; Misiuk, Benjamin; Butschek, Felix; Blondel, Philippe; Montereale-Gavazzi, Giacomo; Lucieer, Vanessa L.; McGonigle, Chris (Frontiers in Remote Sensing, 2025)
IntroductionRemotely-sensed acoustic backscatter is an indispensable tool for seabed mapping, among other disciplines. Almost a decade after the GeoHab Backscatter Working Group published its guidelines and recommendations report, new technologies, new challenges and new questions have emerged. Given the range of potential backscatter research avenues, it can be difficult to align research programs with the priorities of the community of practice. Prioritization of backscatter research topics is thus necessary to establish a roadmap for acoustic backscatter research efforts.MethodsWe asked the international community working with acoustic backscatter to submit their priority research questions over a 5- to 10-year horizon. We analyzed and curated a total of 177 research questions from 73 contributors, and the resulting 104 questions were grouped into eight broad recurring themes: “Technologies”, “Calibration”, “Data acquisition and ground-truthing”, “Data processing”, “Post-processing, quality control, data handling, and curation”, “Data analysis”, “Data interpretation”, and “Applications and end uses”. A follow-up survey based on the final list of questions was distributed to characterize the community working with backscatter and to identify key research priorities.ResultsA total of 120 responses originating from 23 countries were used for the analyses. Most respondents were researchers (68%), while others were technicians (25%) or department or program managers (11%), among other roles. Affiliations of respondents included academia (43%), governmental agencies (37%), and industry/private sector (18%). After scaling the responses, the most commonly selected theme was “Post-processing, quality control, data handling, and curation”, followed by “Calibration” and “Data analysis”. Respondents consistently ranked several research questions as priorities. The two questions that were identified as priorities by over 25% of respondents were “How can we move towards absolute calibration of different systems to allow interregional comparisons?”, and “How can we quantify seafloor backscatter quality and develop standards similar to what exists with bathymetry?”.DiscussionAll eight themes are represented in the top 10 priority questions, underscoring the need for contributions to backscatter research from multiple perspectives to advance the field. The ranking of priority questions encourages collaboration within the community and will serve as a roadmap for backscatter research programs over the next decade.